Development of frozen pork adobo in microwave-safe packaging - Sison, Annabelle Manzano; Franciso, Ma. Leonora dL. (2000.)
ABSTRACT The aim of the study was to develop a frozen Pork Adobo packaged in microwave-safe containers. Phase I determined the most acceptable formulation of Pork Adobo. Results of the sensory evaluation showed that the recipe of Sony Robles-Florendo (1988) was the most acceptable formulation and this was used later in Phase II. Phase II of the study was the lab-scale production, packaging, and freezing of Pork Adobo. Prepared Pork Adobo were placed in microwave-safe containers and kept at low temperature storage for two weeks. Phase III determined the physico-chemical and microbiological characteristics of the product. It was found out that the pH and employment of freezing and microwave reheating prolonged the shelf-life of the product and reduced the incidence of microbial proliferation. Phase IV determined the optimum reheating time through internal temperature measurement and sensory evaluation. From this, it was deduced that the optimum reheating time was seven minutes but it was suggested that thawing be employed first to increase internal temperature.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Frozen foods; Pork adobo